Determinant factors of knowledge management practice: the case of ministry of health, Ethiopia - Nesibu Agonafir Haile; Mekuanint Abera Timbula; Gemechu Abdisa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
This study aims at assessing knowledge management maturity level and the effect of the determinant factors of knowledge management in Ethiopia’s federal ministry of health. Explanatory survey design involving both the quantitative and qualitative methods was employed. General knowledge management maturity model based on people, process and technology key process areas was used to measure knowledge management maturity level in the organization. The qualitative data was analyzed using thematic analysis and summarized under pre identified and emerging themes. The quantitative and qualitative data were triangulated to enrich the findings. The study determined that the ministry’s overall knowledge management maturity level was close to maturity level-2 (Aware), which is generally to mean that the organization was aware of and has the intention to manage its organizational knowledge, but it might not know how to do so. Organizational culture, human resource, information technology and knowledge management process were identified as having significant and positive linear relationship with the knowledge management practice in the organization. It is essential for the ministry to reestablish knowledge management or define improvement plans using model such as the general knowledge management maturity model. The improvement should address the identified determinant factors as well as criterion set for each of the people, process and technology key process areas.